Measurement of near-field radiative heat transfer between plane parallel plates at nano-scale gaps - Webb, Kurt David. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
This thesis establishes a methodology and experimental setup for measuring radiative heat transfer between nano-spaced plane-parallel plates. It uses a setup with two plane-parallel substrates, one heated, one cooled, at a fixed distance from one another. The temperature measurements are carried out by temperature probes on each substrate. The heat flux input is provided by an external focused laser source. The measurement of flux is carried out by diverting a percentage of the incoming light to a photodiode. The stabilization of heat flux is achieved by passive cooling. The measured data are to be evaluated based on its comparison with published numerically calculated results, which indicate an exponential increase in net radiation heat transfer as plate spacing decreases from 100 to 1nm.
Keywords: Nanotechnology.; Heat -- Transmission.